An Evaluation of Asha Worker's Awareness and Practice of Their Responsibilities in Rural Haryana - P K Garg; Anu Bhardwaj; Abhishek Singh; S. K. Ahluwalia (Medsci Publications, 2013)
Introduction- Currently Government of India is providing comprehensive integrated health care to the rural people under the umbrella of National Rural Health Mission (NRHM). A village level community health worker "Accredited Social Health Activist" (ASHA)' acts as an interface between the community and the public health system. Therefore present study was conducted to access the socio-demographic profile of ASHA workers and to assess the knowledge, awareness and practice of their responsibilities. Methodology- The study was conducted in the rural field practice area of the department of community medicine, MMIMSR, Mullana. All 105 ASHA workers in the area were included in the study and were interviewed using a self designed semi-structured questionnaire. Data was analyzed using SPSS and valid conclusions were drawn. Results- Majority of ASHA workers were aware about helping in immunization, accompanying clients for delivery, providing ANC and family planning services as a part of responsibility. Only 17-19% of ASHAs knew about registration of births and deaths, assisting Auxiliary Nurse Midwife (ANM) in village health planning, creating awareness on basic sanitation and personal hygiene. Conclusion- ASHAs do provide constellation of services and play a potential role in providing primary health care but still they need to put into practice their knowledge about while providing services and/or advice to negotiate health care for poor women and children.